2021
DOI: 10.1364/optica.408678
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution imaging for sub-IR frequencies based on total internal reflection

Abstract: For measurements designed to accurately determine layer thickness, there is a natural trade-off between sensitivity to optical thickness and lateral resolution due to the angular ray distribution required for a focused beam. We demonstrate a near-field imaging approach that enables subwavelength lateral resolution in images with contrast dependent on optical thickness. We illuminate a sample in a total internal reflection geometry, with a photoactivated spatial modulator in the near field, which allows optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Another application demonstrated a TIR geometry in a near-field imaging system, in which a spatial modulator was formed by combining a light-sensitive silicon wafer with a prism. This unique combination allowed images of the sample structure to be reconstructed with a subwavelength lateral resolution [ 39 ]. The application of TIR combined with Light-Emitting Diodes (LEDs) effectively enhances the efficiency of light energy, which utilizes the evanescent wave in a TIR setup coupled with a conductive interface [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another application demonstrated a TIR geometry in a near-field imaging system, in which a spatial modulator was formed by combining a light-sensitive silicon wafer with a prism. This unique combination allowed images of the sample structure to be reconstructed with a subwavelength lateral resolution [ 39 ]. The application of TIR combined with Light-Emitting Diodes (LEDs) effectively enhances the efficiency of light energy, which utilizes the evanescent wave in a TIR setup coupled with a conductive interface [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…This requirement for free-space propagation places limits on the minimum operational volume of a wide range of optical elements and devices, such as cameras, microscopes, telescopes and spectrometers. The issue of size becomes even more prominent at longer wavelengths in so-called quasi-optical systems common to the terahertz [1], millimetre-wave [2] and microwave domains [3]. In this regime, free-space diffraction is fundamental to the operation of antennas [4][5][6][7] and beam waveguides [8], and this can lead to very large optical systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…Single-pixel THz cameras do exist 10,11 and they have been used for inspection of circuits hidden behind semiconductors, 12 for example, as well as for near-field THz imaging of solid state systems 13−16 and biological samples as well. 17 There have also been studies showing 2D tomographic imaging 18 and potential for standoff applications. 19 Previously, we showed that a THz video can be obtained and displayed in real-time with a single-pixel THz camera.…”
mentioning
confidence: 99%
“…This makes them highly suited for THz imaging. Single-pixel THz cameras do exist , and they have been used for inspection of circuits hidden behind semiconductors, for example, as well as for near-field THz imaging of solid state systems and biological samples as well . There have also been studies showing 2D tomographic imaging and potential for standoff applications .…”
mentioning
confidence: 99%
See 1 more Smart Citation